QAWL AL-SAHĀBIYY SEBAGAI SUMBER HUKUM:TUMPUAN KEPADA KES-KES FARĀ’ID TERTENTU: The Fatwa of a Companion as Sources of Islamic Law in the Specific Cases on Farā’id - Mahad Musa, Zahari (Jurnal Syariah, 2012)
The fatwa of a companion, as one of the disputed sources of Islamic law, has its role in explaining law derived from Ijtihad that is formulated by the companion. The two main functions of this Ijtihad are to reinterpret law that is available in the legal text and to explicate something new without going against the Islamic law. This article aims to elucidate its definition and the opinion of the principles of Islamic jurisprudence scholars on matters relating thereto. The discussion is also centred on the specific cases on farā’id, which is well-known for its particular name and calculation that made it famous. Four cases have been chosen as samples – al-musharrakah case, al-kharqa’ case, al-akdariyyah case and al-hamziyyah. Generally, the authority for deriving Ijtihad focuses more on the individuals who were frequently referred to in issuing a fatwa. In addition, the role of Ijtihad of a companion in elaborating a law is very important even though it has already been detailed in legal text.